Involving service users in Births and their outcomes: a retrospective birth cohort data linkage study analysing daily, weekly and yearly cycles and their implications for the NHS - Newburn, Mary; Scanlon, Miranda; Plachcinski, Rachel; Macfarlane, Alison Jill (International Journal of Population Data Science, 2020)
Introduction We report on service user participation in ‘Births and their Outcomes’, a population-based, retrospective, birth cohort, data linkage study to analyse the daily, weekly and yearly cycles of births and their implications for the NHS. Although Public Involvement and Engagement (PI&E), also referred to here as Patient and Public Involvement (PPI), has a long history in maternity services, PI&E in maternity data linkage studies is new. We have reported using the GRIPP2 short form. Objectives We aimed to involve and engage a wide range of maternity service users and their representatives to ensure that our use of routinely collected maternity and birth records was acceptable and that our research analyses using linked data were relevant to their expressed safety and quality of care needs. Methods A three-tiered approach to PPI was used. Having both PPI co-investigators and PPI members of the Study Advisory Group ensured service user involvement was part of the strategic development of the project. A larger constituency of maternity service users was engaged through four workshops held throughout England. Results Two co-investigators with experience of PPI in maternity research were involved from design stage to dissemination. Four PPI study advisors contributed service user perspectives. Engagement workshops attracted around 100 attendees, recruited largely from Maternity Services Liaison Committees and a community engagement group. They supported use of the data, believing the study had potential to improve safety and quality of maternity services. They contributed their experiences and concerns which will assist with interpretation of the analyses. Conclusion Use of PPI ‘knowledge intermediaries’ successfully bridged the gap between data intensive research and lived experience, but more inclusivity in involvement and engagement is required. The concerns and questions of service users provide social legitimacy and a relevance framework for researchers carrying out analyses.